Investigating the Health Diet Needs of Diabetic Elderly in Daily Life: A Systematic Review - Jinglong, Li; Che Me, Rosalam; Arif Ahmad, Faisul; Qisen, Zhu (Edelweiss Applied Science and Technology, 2024)
Diabetes has increasingly affected populations over the decades, particularly among elderly groups. Maintaining a healthy diet is crucial for managing diabetes, yet elderly people with diabetes often exhibit poor dietary habits. Therefore, this paper aims to investigate the dietary needs of elderly individuals with diabetes to provide comprehensive guidance for improving their dietary habits and overall diabetes management. A systematic review approach was adopted in this study, three reference databases, Scopus, Web of Science, and PubMed were consulted; 28 articles were screened in the final data code and analysis. Results found that four important needs among diabetic elderly include healthy diet knowledge, dietary suggestions, glucose monitoring, and physical activity. Those findings reveal the significance of diabetes management, underscoring the need for targeted educational interventions. Personalized nutrition plans and user-friendly glucose monitoring technologies are essential for improving dietary adherence and blood glucose control. Barriers to regular physical activity, including mobility issues and fear of injury, highlight the need for tailored, enjoyable exercise programs. Addressing these issues through holistic and individualized approaches can enhance diabetes management and health outcomes for this population. The study emphasizes the need for healthcare providers to develop and implement personalized nutrition plans, user-friendly glucose monitoring devices, and tailored exercise programs to support better diabetes management in the elderly population. Future research should focus on creating and testing these user-friendly products to further enhance care for this vulnerable group.